Preferential hyperacuity perimeter in the study of diabetic macular edema - Matos, Ana Cláudia Moreira Rebelo de (2012)
Introduction – Preferential hyperacuity perimeter (PHP) is a new psychophysical test, which principle is based on the detection of metamorphopsia in age-related macular degeneration (AMD). It is intended to verify its effectiveness in the study of diabetic macular edema (DME). When there is a loss of pericytes in the vascular wall occur a number of microcirculatory changes that lead to the appearance of microaneurysms and other vascular changes that allow the passage of blood components to the surrounding retinal tissue in a normal situation do not occur, these being one of the causes exudative diabetic macular edema. Methodology – It was performed a quantitative study, using descriptive and correlational analysis. A sample of 33 patients was selected, and 60 eyes were analyzed. Results – The sensitivity of PHP on the detection of metamorphopsia associated with EMD was 70.6%, the specificity was 11.5% and the global efficiency of the test was 45%. It was found a weak negative correlation (Phi= -0.215) between the PHP and optical coherence tomography (OCT). Conclusions – This new method of diagnosis was sensitive, but not very specific and effective in the detection of metamorphopsia, due to the DME.